Sambhāvane : Rājasēvāsakta Beḷḷūra Mailāra Śrīkaṇṭhayyanavarige avara śiśyarū mitrarū oppisida prabandhagaḷa saṃpuṭa - Srikantayya, B. M., 1884-1946 (Kannaḍa Sāhitya Pariṣattu, 1979)
Articles on Kannada literature and the services to Kannada culture of B.M. Srikantayya, 1884-1946, Kannada writer; a festschrift.